Economic analysis on the causes of mental health stress of enterprise employees based on emotional feature clustering - Li, Benqing; Qiao, Yajie (Frontiers in Psychology, 2022)
Emotional labor generally exists in organization members. Emotional labor will not only affect employees' interpersonal relationships, but also affect employees' mental health. Affected by many factors such as the economic environment, they often need to bear multiple pressures. The degree of stress is positively correlated with the depth of the development of the times and people's education. As mental health research has become the frontier and hot spot in the field of psychology, the role of mental health in the process of employee creativity has been paid more and more attention. Therefore, this paper proposes a study on the causes of employees' psychological stress based on emotional feature clustering. Based on the clustering of emotional characteristics, this paper analyzes the causes of employees' mental health stress from an economic perspective. For teams with low level of team openness, with the improvement of team heterogeneity, team task performance shows a slight upward trend. It is clear from the experiment that when the number of experiments reaches 100, the task performance of high atmosphere level is 12.14, while the task performance of low atmosphere level is only 9.89. Therefore, the atmosphere of team employees is very important to team task performance. Through the cluster analysis of employees' mental health characteristics, it not only increases employees' spare time life, but also reduces employees' daily contradictions. It eases the work pressure of employees, and becomes a platform for employees to improve their awareness and a promoter of harmonious employee relations.